2018
DOI: 10.3390/nu10111692
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Smartphone Application Can Improve Assessment of High-Fat Food Consumption in Overweight Individuals

Abstract: Background: We evaluated the feasibility of an application for measuring the frequency of consumption of high-fat foods and compared this application with standard methods. Methods: Twenty-six females and thirty six males aged 20–40 were enrolled in Poland. Participants completed the Block Screening Questionnaire for Fat Intake (BSQF; Q1) and a second questionnaire (Q2) with additional high-fat foods. The participants were then monitored for ten days in a real-time manner using a smartphone application that em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 42 publications
(48 reference statements)
0
44
0
Order By: Relevance
“…The first thing we noticed was that few studies validated EMA protocols against current dietary assessment methods or nutritional markers. Among these, Chmurzynska and colleagues compared the feasibility of a signal-contingent EMA protocol for measuring the frequency of consumption of high-fat foods with standard retrospective methods, such as the Block Screening Questionnaire for Fat Intake [20]. Interestingly, they reported that using EMA improved the assessment of dietary data, especially in overweight or obese individuals [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first thing we noticed was that few studies validated EMA protocols against current dietary assessment methods or nutritional markers. Among these, Chmurzynska and colleagues compared the feasibility of a signal-contingent EMA protocol for measuring the frequency of consumption of high-fat foods with standard retrospective methods, such as the Block Screening Questionnaire for Fat Intake [20]. Interestingly, they reported that using EMA improved the assessment of dietary data, especially in overweight or obese individuals [20].…”
Section: Resultsmentioning
confidence: 99%
“…Among these, Chmurzynska and colleagues compared the feasibility of a signal-contingent EMA protocol for measuring the frequency of consumption of high-fat foods with standard retrospective methods, such as the Block Screening Questionnaire for Fat Intake [20]. Interestingly, they reported that using EMA improved the assessment of dietary data, especially in overweight or obese individuals [20]. Next, Bucher Della Torre and colleagues developed the electronic carnet alimentaire (e-CA)—“food record” in French—which included approximately 900 foods and beverages classified in 14 categories [19].…”
Section: Resultsmentioning
confidence: 99%
“…Although the interactions between frequent high-fat food consumption and obesity, and the interactions between frequent high-fat food consumption and dyslipidemia have rarely been reported, Chmurzynska et al reported that the frequency of consumption of high-fat foods was correlated in the obesity [28]. Moreover, studies have shown that the interaction between a low-fat diet, such as a Mediterranean diet, and genetic factors have impact on the risk for CHD [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…This is also the rst study to assess eating behavior with two different procedures: a buffet test-meal (experimental setting) and a food diary using a mobile app (real-world setting). Previous studies assessed eating behavior by applying only a single method, either an experimental test meal 33 or a food diary app 34 . Studies assessing eating behavior with laboratory meals showed higher reliability and validity, but insu ciently re ected real-world eating behaviors.…”
Section: Methodology: Buffet Test-meal and Food Diary In Appmentioning
confidence: 99%